2009
DOI: 10.1002/elps.200800717
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic peas expressing an α‐amylase inhibitor gene from beans show altered expression and modification of endogenous proteins

Abstract: Differential in-gel electrophoresis showed contrasting effects of the transgenic expression of an alpha-amylase inhibitor from beans on the proteomes of two pea cultivars. One cultivar showed minor changes relative to its non-transgenic parent with only one protein changing by more than about twofold. Changes in the abundance of certain endogenous proteins in the other cultivar were of greater number and magnitude with some endogenous proteins undetected while some new protein spots appeared in the transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…It was concluded that the proteomics differences between transgenic and non-transgenic plants were more likely due to physiological variations. This conclusion was confirmed by another study of the effects of transgenic aAI on proteomes of two pea cultivars carried out by 2D-DIGE (Islam et al, 2009). These authors found that even transformed with the same gene, two transgenic cultivars showed no (at least little) common alterations of protein profiles.…”
Section: H Assessing the Equivalence Of Genetically Modified Cropssupporting
confidence: 55%
“…It was concluded that the proteomics differences between transgenic and non-transgenic plants were more likely due to physiological variations. This conclusion was confirmed by another study of the effects of transgenic aAI on proteomes of two pea cultivars carried out by 2D-DIGE (Islam et al, 2009). These authors found that even transformed with the same gene, two transgenic cultivars showed no (at least little) common alterations of protein profiles.…”
Section: H Assessing the Equivalence Of Genetically Modified Cropssupporting
confidence: 55%
“…However the commercial development of these lines was abandoned when transgenic seeds appeared to invoke a T-cell response in mice which was not evident when either of the non-transgenic pea or bean seeds were tested. This observation and subsequent studies led to the conclusion that differential glycosylation of the α-amylase inhibitor Downloaded by [West Virginia University] at 06:35 20 November 2014 expressed in the non-host plant had triggered a pre-immune response (Editorial, 2006); other minor changes to seed proteins were also documented for the transgenic seeds, likely reflecting pleiotropic effects on post-translational processing (Islam et al, 2009) as noted also for other organs and species (Lehesranta et al, 2005).…”
Section: E the Anti-nutritional Factor Riddle In Legumesmentioning
confidence: 88%
“…Analyzing two pea (Pisum sativum) cultivars producing a bean (Phaseolus vulgaris) a-amylase inhibitor (AI1), Islam et al (2009) found around 30 seed protein spots showing changes in abundance in each transgenic/control pair (generally not the same spots, although AI1 was produced at similar levels in both cultivars). While differences were minor for one pair, they were more pronounced quantitatively and qualitatively (appearance and disappearances of 36 protein spots) for the second pair.…”
Section: Peamentioning
confidence: 99%